The Girl Who Wanted A Lion for a Pet - Okoro, Emmanuel (Nigeria, 2016)
'The Girl Who Wanted a Lion for a Pet'' tells a story about a young girl Ralia who overcame the pangs of peer pressure to set and achieve a truly SMART goal through the help of her parent, History teacher and Mathematics teacher...
Keywords: Adventure; Juvenile Fiction